Acute treatment with the PDE4 inhibitor roflumilast improves verbal word memory in healthy old individuals: a double-blind placebo-controlled study - Blokland, Arjan; Van Duinen, Marlies A.; Sambeth, Anke; Heckman, Pim R.A.; Tsai, Max; Lahu, Gezim; Uz, Tolga; Prickaerts, Jos (Neurobiology of aging, 2019)
There is ample evidence that phosphodiesterase 4 (PDE4) inhibition can improve memory performance in animal studies. In the present study, we examined the acute effects of the PDE4 inhibitor roflumilast on memory performance in healthy individuals (60–80 years of age). We tested the effects of acute roflumilast administration (100, 250, 1000 μg) in a double-blind, placebo-controlled, 4-way crossover design. Participants were first screened for their verbal word memory performance to ensure normal memory performance (within 0.5 standard deviation from norm score; n = 20) Drug effects on memory performance were tested in a verbal memory test and a spatial memory test. Reported side effects of drug treatment were registered. Roflumilast (100 μg) improved the delayed recall performance of the participants (Cohen's d, 0.69). No effects were observed in the spatial memory task. Roflumilast was well tolerated at this low dose. Although no clear adverse side effects were reported at the low dose, mild adverse events (including headache, dizziness, insomnia, and diarrhea) were reported after the 1000 μg dose. The present study provides first evidence that the PDE4 inhibitor roflumilast improves verbal memory performance in old participants. The current data encourage further development of PDE4 inhibitors for improving memory. •Phosphodiesterase type 4 (PDE4) breaks down cAMP, which plays a crucial role in neuronal plasticity.•A vast amount of animal studies has shown improved learning and memory with PDE4 inhibitors.•The PDE4 inhibitor roflumilast improved the delayed verbal memory recall in healthy old participants.